2017
DOI: 10.1007/s00203-017-1419-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial activity of a blend of monoglycerides against Escherichia coli and Enterococci with multiple drug resistance

Abstract: Bacterial antibiotic resistance is a natural phenomenon, seriously affecting the treatment of infections. The biggest danger is that current antibiotics are not able to eradicate the resistant strains. In recent years, alternative antibacterial substances are being sought, which can help in these cases. Fatty acids and monoglycerides are known among the natural substances for their antimicrobial properties and, important detail, bacteria do not develop resistance to them. In this work, we studied the antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
2
5
0
1
Order By: Relevance
“…These observations are consistent with a study reported by Anacarso et al [35], in which 37 E. coli strains were highly susceptible to a blend containing monolaurin and monobutyrin, although the antimicrobial activity was not tested with individual monoglycerides in this study. In agreement with previously published research [35,41,42], the present study demonstrated that G+ bacteria were more susceptible to monolaurin than G− bacteria, with MIC values from 10 to 500 mg/L against G+ bacteria and MIC values from 600 to 10,000 mg/L against G− bacteria. It has also been reported that monolaurin actively inhibited the growth of Staphylococcus, Streptococcus , Bacillus , and several other G+ bacterial strains with relatively low MIC values [37,43].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These observations are consistent with a study reported by Anacarso et al [35], in which 37 E. coli strains were highly susceptible to a blend containing monolaurin and monobutyrin, although the antimicrobial activity was not tested with individual monoglycerides in this study. In agreement with previously published research [35,41,42], the present study demonstrated that G+ bacteria were more susceptible to monolaurin than G− bacteria, with MIC values from 10 to 500 mg/L against G+ bacteria and MIC values from 600 to 10,000 mg/L against G− bacteria. It has also been reported that monolaurin actively inhibited the growth of Staphylococcus, Streptococcus , Bacillus , and several other G+ bacterial strains with relatively low MIC values [37,43].…”
Section: Discussionsupporting
confidence: 94%
“…However, monopropionin has weaker antimicrobial activities against G− and G+ bacteria compared with monobutyrin and monovalerin. Results of the present study were consistent with previously published research that indicated monobutyrin had antimicrobial effects on many E. coli strains, S. Typhimurium, and C. perfringens strains in vitro [25,35].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, Nakatsuji et al explored the feasibility of employing LA to treat a mouse model infection caused by another Gram-positive bacterium, specifically Propionibacterium acnes [ 20 ]. Hence, multiple antimicrobial lipids have shown in vivo therapeutic potential, and there is also growing interest to investigate combinations of several antimicrobial lipids that have antibacterial potency against specific bacteria in order to achieve synergistic and broad-spectrum effects [ 85 , 86 , 87 , 88 , 89 ].…”
Section: Antimicrobial Lipidsmentioning
confidence: 99%
“…Further, 5-hydroxymethyl furfural is reported to have antibacterial properties (Kim et al 2009). In addition, some short-and medium-chain fatty acids like capric acid and butanoic acid have also displayed antibacterial and cell envelope destructive activities against MDR E. coli and H. pylori, respectively (Anacarso et al 2018;Yonezawa et al 2012). Similarly, hexanedioic acid, hexadecanoic acid and heptadecanoic acid have been reported as potent antimicrobial and antifungal agents (Choi and Jiang 2014;Moon and Cha 2020;Selvi et al 2020).…”
Section: Gc-ms Analysis Of Vpementioning
confidence: 99%